Unveiling the characteristics of MgAl0.5Fe1.5O4 spinel ferrite: A study of structural, optical, and dielectric properties - Verma S.; Maurya A.; Verma H.; Singh R.; Bhoi B. (My University, 2025)
Aluminium-doped magnesium ferrite (MAFO) has garnered significant interest due to its recently observed low microwave loss properties, making it invaluable for applications at high-frequency operations, including fields like spintronics and magnonics. This study delves into the optical and dielectric properties of MgAl0.5Fe1.5O4 synthesized via a conventional solid-state method followed by sintering at 1350 °C for 6 hrs. The X-ray diffraction analysis confirmed the formation of pure, single-phase MAFO spinel ferrite with the lattice constant of 8.313 Å. The Williamson–Hall (W-H) method was employed to determine the crystallite size and strain from X-ray diffraction data, resulting in values of 115.4 nm and 9.37 × 10–4, respectively. UV–visible spectroscopy was used to determine the optical properties, revealing a band gap of 2.38 eV and an average refractive index of 2.09 for the investigated spinel ferrite. The dielectric properties including capacitance, dielectric constant (ε), dielectric loss, ac conductivity, complex impedance, and modulus of MAFO sample were studied as a function of frequency for various temperatures. This comprehensive analysis sheds light on the previously undiscovered traits in the material's transport phenomena and optical attributes, opening an exciting and active field of research into its other physical properties. © 2024 The Authors